Aberrant Expression of Nucleostemin Activates p53 and Induces Cell Cycle Arrest via Inhibition of MDM2 - Dai, Mu-Shui (American Society for Microbiology (ASM), 2008)
The nucleolar protein nucleostemin (NS) is essential for cell proliferation and early embryogenesis. Both depletion and overexpression of NS reduce cell proliferation. However, the mechanisms underlying this regulation are still unclear. Here, we show that NS regulates p53 activity through the inhibition of MDM2. NS binds to the central acidic domain of MDM2 and inhibits MDM2-mediated p53 ubiquitylation and degradation. Consequently, ectopic overexpression of NS activates p53, induces G(1) cell cycle arrest, and inhibits cell proliferation. Interestingly, the knockdown of NS by small interfering RNA also activates p53 and induces G(1) arrest. These effects require the ribosomal proteins L5 and L11, since the depletion of NS enhanced their interactions with MDM2 and the knockdown of L5 or L11 abrogated the NS depletion-induced p53 activation and cell cycle arrest. These results suggest that a p53-dependent cell cycle checkpoint monitors changes of cellular NS levels via the impediment of MDM2 function.